Α-Enolase Causes Proinflammatory Activation of Pulmonary Microvascular Endothelial Cells and Primes Neutrophils Through Plasmin Activation of Protease-Activated Receptor 2. Issue 2 (August 2015) - Bock, Ashley; Tucker, Nicole; Kelher, Marguerite R.; Khan, Samina Y.; Gonzalez, Eduardo; Wohlauer, Max; Hansen, Kirk; Dzieciatkowska, Monika; Sauaia, Angels; Banerjee, Anirban; Moore, Ernest E.; Silliman, Christopher C.
Abstract : ABSTRACT: Proinflammatory activation of vascular endothelium leading to increased surface expression of adhesion molecules and neutrophil (PMN) sequestration and subsequent activation is paramount in the development of acute lung injury and organ injury in injured patients. We hypothesize that α-enolase, which accumulates in injured patients, primes PMNs and causes proinflammatory activation of endothelial cells leading to PMN-mediated cytotoxicity.Methods : Proteomic analyses of field plasma samples from injured versus healthy patients were used for protein identification. Human pulmonary microvascular endothelial cells (HMVECs) were incubated with α-enolase or thrombin, and intercellular adhesion molecule-1 surface expression was measured by flow cytometry. A two-event in vitro model of PMN cytotoxicity HMVECs activated with α-enolase, thrombin, or buffer was used as targets for lysophosphatidylcholine-primed or buffer-treated PMNs. The PMN priming activity of α-enolase was completed, and lysates from both PMNs and HMVECs were immunoblotted for protease-activated receptor 1 (PAR-1) and PAR-2 and coprecipitation of α-enolase with PAR-2 and plasminogen/plasmin.Results : α-Enolase increased 10.8-fold in injured patients ( P < 0.05). Thrombin and α-enolase significantly increased intercellular adhesion molecule-1 surface expression on HMVECs, which was inhibited by antiproteases, induced PMN adherence, and served as the first event in the two-event model of PMN cytotoxicity. α-Enolase coprecipitated with PAR-2 and plasminogen/plasmin on HMVECs and PMNs and induced PMN priming, which was inhibited by tranexamic acid, and enzymatic activity was not required.Conclusions : α-Enolase increases after injury and may activate pulmonary endothelial cells and prime PMNs through plasmin activity and PAR-2 activation. Such proinflammatory endothelial activation may predispose to PMN-mediated organ injury.